1975
DOI: 10.1080/00039896.1975.10666733
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ability of Workmen Occupationally Exposed to Lead

Abstract: The reproductive ability of 150 men occupationally exposed to lead were studied by clinical and toxicological analysis. Subjects were divided into four groups: lead-poisoned workmen (23) and those showing a moderate (42), slight (35), or physiologic absorption (50). Findings show that (1) Lead poisoning as well as moderate increased absorption of lead decrease the fertile ability of men. An increased frequency of asthenospermia, hypospermia, and teratospermia have objectified the decrease. (2) Slight increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1
6

Year Published

1979
1979
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(163 citation statements)
references
References 16 publications
5
151
1
6
Order By: Relevance
“…This heavy use of lead in industries has caused the contamination of air, dust, and soil. Lead toxicity is associated with a variety of dysfunctions in experimental animals and humans (Hsu and Leon 2002) including haemopoietic system (De Silva 1981), liver (Sharama and Street 1980), kidneys (Humphreys 1991;Hernberg 2000), male and female reproductive systems (Lancranjan et al 1975;Rom 1980). Several review reports on lead toxicity and its possible mechanisms of action are available in literature (Gurer and Ercal 2000;Hernberg 2000;Hsu and Leon 2002;Meyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This heavy use of lead in industries has caused the contamination of air, dust, and soil. Lead toxicity is associated with a variety of dysfunctions in experimental animals and humans (Hsu and Leon 2002) including haemopoietic system (De Silva 1981), liver (Sharama and Street 1980), kidneys (Humphreys 1991;Hernberg 2000), male and female reproductive systems (Lancranjan et al 1975;Rom 1980). Several review reports on lead toxicity and its possible mechanisms of action are available in literature (Gurer and Ercal 2000;Hernberg 2000;Hsu and Leon 2002;Meyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lead exposure is associated with neurologic (3-6), growth (3,7), and reproductive defects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Lead exposure in men has been associated with abnormalities of spermatogenesis (9,(11)(12)(13)).…”
mentioning
confidence: 99%
“…1 mpairment of reproduction in men exposed occupationally to lead has been reported in severa 1 papers. Lancranjan et al (1975) found increased frequency of asthenospermia, hypospermia and teratospermia in 16 workers with lead poisoning (blood lead JeveJ, 745 i: 260 t.g/I) and in 29 with moderately increased absorption (bJood lead leveJ, 528 i: 210 t.g/I), but not in 50 with 'normal' absorption (blood lead leveJ, 230 i: 150 t.g/I).…”
Section: Route and Dosagementioning
confidence: 99%